PENGARUH KOMPOSISI PROBIOTIK YANG BERBEDA PADA PAKAN BUATAN TERHADAP RASIO KONVERSI PAKAN DAN LAJU PERTUMBUHAN BENIH IKAN GABUS LOKAL (Channa sp) HASIL DOMESTIKASI - Fazril Saputra; Yusran Ibrahim (JURNAL PERIKANAN TROPIS, 2021)
Snakehead fish (Channa sp.) was one of Indonesia's native freshwater commodities that has been successfully domesticated by fish cultivators in Indonesia. However, domesticated snakehead fish cultivation still has obstacles, namely the high value of the feed conversion ratio and the low growth rate of local snakehead fish. Overcoming this problem requires a technology that can optimize the feed conversion ratio and growth rate of domestic snakehead fish. One technology that can be applied is the used of probiotic technology. This study aims to test the provision of different probiotics through feed to optimize the feed conversion ratio and growth rate of domestic snakehead fish. This research was conducted using experimental methods. The experimental design used was a completely randomized design with 4 treatments and each treatment was repeated 3 times. The treatments were treatment without probiotics / control (P0), treatment of the probiotic composition of Lactobacillus sp., Bacillus spp. and Nitrosomonas sp. (P1), treatment of the probiotic composition of Lactobacillus casei and Saccharomyces cerevisiae (P2), treatment of the probiotic composition of Lactobacillus sp., Acetobacter, Rhodobacter sp., Yeast (P3). The results showed that giving different probiotic compositions through feed on the parameters of feed conversion ratio and growth rate did not give results that were not significantly different (P> 0.05) when compared to control, but the highest treatment value was found in the probiotic composition of Lactobacillus casei and Saccharomyces cerevisiae.